From Laboratory to Field: Notes on Studying Diversity in Israeli Society - Goldberg, Harvey E.; Salamon, Hagar (Hagar: Studies in Society and Culture, 2002)
The paper presents a research path capable of com- prehending the dynamics of diversity within Israeli society. It re- views earlier research paradigms as well more recent analytic stances that stress the society’s fragmentation into disparate units. The research approach seeks to identify themes that run through Israeli culture even as they are subjects of difference and conflict. It stresses the importance of ethnography while theoretically ex- panding the notion of “field” to encompass historical and cul- tural factors that enter into complex social situations.